Formatting, Printing, and Reporting with Oracle Primavera P6 PPM - Harris, Paul (Packt Publishing, 2021)
Primavera P6 Version 8 to Version 20, this module explains the differences between the versions About This Video Workshop on formatting the bar chart and organizing your data Workshop on filters and printing Workshop on activity codes and User-Defined Fields (UDF) In Detail Primavera is an enterprise project portfolio management software. It includes project management, scheduling, risk analysis, opportunity management, resource management, collaboration, and control capabilities, and integrates with other enterprise software such as Oracle and SAP's ERP systems. This course aims to teach participants how projects are planned, scheduled, and controlled, including understanding the project management processes applicable to your projects with Oracle Primavera P6 PPM Professional. You will start with understanding the basics of the software. Moving ahead, you will look at formatting the display aspects of the software. Then you will look at the group, sort, and layouts of this tool. Following that, you will understand, apply, create, and modify filters. After that, you will execute printing, reports, and look at the visualizer. Finally, you will explore other methods of organizing project data. By the end of the course, you will successfully learn how to format, print, and run reports with Oracle Primavera Project Manager P6 PPM Professional Client.